Antioxidative activities and isolation of phenolic compounds from the root, fruit and leaf of Mengkudu (Morinda citrifolia L.) - Mohd Zin, Zamzahaila (2003)
This study was conducted with the objective of evaluating the antioxidative activities of extracts from different parts of Mengkudu (Morinda citrifolia L.) including leaf, fruit and root Methanol, petroleum ether, water and ethyl acetate were used as extraction solvent. The anti oxidative activities assays were done using ferric thiocyanate method (FTC) and thiobarbituric acid test (TBA). Furthermore, the activities of these extracts were then compared to that of a-tocopherol and butylated hydroxyl tolune (BHT). Effect of solvent types and concentration of extract used on antioxidative activities of M. citrifolia were also carried out. Meanwhile, isolation of phenolic compounds was carried out using Sephadex LH-20 column chromatography. Identification and quantification of the common flavonoids in the separated fractions were carried out using a reversed phase high-performance liquid chromatography (RP-HPLC) procedures on a Symmetry CIS colwnn with water-methanol gradient elution system. Results showed that methanol root extract exhibited higher activity compared to that of fruit and leaf extract of the same with no significant (p<O.05) difference as compared to that of a-tocopherol and BHT. The result also showed that methanol gave highest yield of extract compared to that of water, petroleum ether and ethyl acetate extraction. Meanwhile, both polar and non-polar extract of M citrifolia L. exhibited appreciable activity. Increasing concentration of methanol root extracts from 1000 to 5000 ppm do not significantly increased the anti oxidative activity. On the other hand, there was significant (p<0.05) difference in antioxidative activities of methanol leaf and fruit extracts when concentrations were increased. Similarly, increasing concentrations of water extracts from 1000 to 5000 ppm do not significantly increased the antioxidative activity of root and leaf of M cirrifolia L. However, there was significant (P<0.05) difference in anti oxidative activities of fruit extract at 1000 ppm compared to 2000 ppm. At 3000 ppm onwards there were no significant (p<0.05) difference in activities. Result also showed that at 3000 ppm, water extract of root, fruit and leaf of M citrifolia L. exhibited no significant (p<0.05) difference in activities dum that of either a -tocopherol or BHT. Meanwhile, increasing concentration of petroleum ether extract significantly increased the anti oxidative activity of all parts of M citrifolia. The result also revealed that the antioxidative activities exhibited by petroleum ether root extract was significantly (p<0.05) higher than that of either a -tocopherol or BHT at concentration more than 4000 ppm. Similar observation was found in fruit and leaf extract of same solvent at 5000 ppm, where fruit and leaf extract exhibited significantly (p<0.05) higher activity than that of either a -tocopherol or BHT. Increasing concentration of ethyl acetate leaf extract from 1000 ppm to 5000 ppm do not significantly increased the antioxidative activities. On the other hand, at 3000 ppm onwards there was significant (p<0.05)difference in anti oxidative activities of root and fruit extracts when concentrations were increased. Result also showed that at 3000 ppm and 4000 ppm, there was no significant (P<0.05) difference in the activities exhibited by root and leaf extract of same solvent than that of either (l -tocopherol or BHT. Meanwhile ethyl acetate fruit extract exhibited significantly higher activity than that of either (l-tocopherol or BHT at the same concentration tested. From this study it can be seen that different parts of M citrifolia exhibited varying degrees of antioxidative activities when different solvents were used in extraction procedures. Of the four solvents used, ethyl acetate is the best solvent for extracting antioxidative compounds from different parts (root, fruit and leaf) of Morinda citrifolia L. compared to other solvent. Isolation of phenolic compounds mainly focused on the separation and identification of antioxidants from methanol extract because of the polar properties of phenolic compounds especially flavonoids, which are known to be potent antioxidant. All fractions were seen to contain different amount of total phenolic compound and exhibited considerably high antioxidative activity. Identification of flavonoid successfully determines the individual active compound present in M citrifolia. Major component determine including catechin and epicatechin, which are known to be potent antioxidant.